Dynamic Changes of Brain Activity in Patients With Disorders of Consciousness During Recovery of Consciousness - Guo, Yongkun; Li, Ruiqi; Zhang, Rui; Liu, Chunying; Zhang, Lipeng; Zhao, Dexiao; Shan, Qiao; Wang, Xinjun; Hu, Yuxia (Frontiers in Neuroscience, 2022)
The disorder of brain activity dynamics is characteristic leading to disorders of consciousness (DOC). However, few studies have explored whether the dynamics of brain activity can be modulated, and whether the dynamics of brain activity can help to evaluate the level of consciousness disorder and the effect of consciousness recovery. Twenty patients with minimally conscious state (MCS) and 13 patients with vegetative state (VS) were enrolled, and resting state electroencephalogram (EEG) data and the coma recovery scale-revised (CRS-R) scores were collected three times before and after high-definition transcranial direct-current stimulation (HD-tDCS) treatment. The patients were divided into the improved group and the unimproved group according to whether the CRS-R score was improved after treatment, and the dynamic changes of resting state EEG microstate parameters during treatment were analyzed. The results showed the occurrence per second (OPS) of microstate D was significantly different between the MCS group and VS group, and it was positively correlated with the CRS-R before treatment. After 2 weeks of HD-tDCS treatment, the OPS of microstate D improved significantly in the improved group. Meanwhile, the mean microstate duration (MMD) and ratio of time coverage (Cov) of microstate C, and the Cov of microstate D were significantly changed after treatment. Compared with the microstate parameters before treatment, the dynamic changes of parameters with significant difference in the improved group showed a consistent trend after treatment. In contrast, the microstate parameters did not change significantly after treatment in the unimproved group. The results suggest that the dynamics of EEG brain activity can be modulated by HD-tDCS, and the improvement in brain activity dynamics is closely related to the recovery of DOC consciousness, which is helpful to evaluate the level of consciousness disorder and the effect of consciousness recovery.